Transformasi Digital Peradilan Solusi Fenomena “No Viral No Justice” - Nabilla Syifa Auliya; Fadlah Nur; Siti Zahra (Proceeding of the International Conference on Global Education and Learning, 2025)
The hastag No. viral No. justice has recently emerged on social media platforms creating its own discourse in the justice system. This research aims to examine how the impact of this phenomenon on the judicial system and to find the ideal mechanism of digital transformation of justice so that this phenomenon remains in line with the principle of due process of law.This research method uses a social legal with a case study approach and conceptual approach in answering the problem formulation. This research found that this phenomenon is motivated by the slow response of law enforcement officials and the lack of transparency of the judicial system, then the impact of this phenomenon disrupts the independence of the judiciary because it is tried by the media and has the potential to accommodate the spread of hoaxes and public disinformation. To answer these challenges, the author proposes a digital transformation of the judiciary through the optimization of SIPP, by adding a verification link feature on the SIPP page. So that access to case tracking becomes more transparent. In addition, there are also new rules regarding the publication of unresolved legal cases on social media by requiring the admin and related accounts to provide a disclaimer and link to the SIPP verification link of the case. This regulation is regulated through the revision of the ITE Law by the legislators.